Comparative retrospective study on surgical outcomes of hand‐sewn anastomosis versus stapling anastomosis for colectomy using a nationwide inpatient database in Japan with propensity score matching - Shota Ebinuma; Susumu Kunisawa; Kiyohide Fushimi; Nobuki Ichikawa; Tadashi Yoshida; Shigenori Homma; Akinobu Taketomi; Yuichi Imanaka (Annals of Gastroenterological Surgery, 2025)
Abstract Background Intestinal anastomosis is performed by two main methods: hand‐sewn anastomosis (HA) and stapling anastomosis (SA). Studies on anastomosis are still being reported and are an ongoing area of interest. The aim of this study was to evaluate the characteristics of each by comparing them with description and statistical analysis using a nationwide inpatient database. Methods We collected data for colon cancer patients who underwent colectomy between April 2014 and March 2022 using the Diagnosis Procedure Combination (DPC) database. In the descriptive analysis, we described the background of the study population and the number of each method. In the statistical analysis, we used propensity score matching to achieve balanced covariates and showed the results of the comparative study using risk ratios and risk differences. Results A total of 232 155 cases were selected (HA group: 40 764; SA group: 191 391). SA was performed more frequently than HA during the study period, with the proportion of SA increasing over the last few years (~80% in 2015 and 85% in 2021). We obtained 40 760 pairs through propensity score matching. The comparison of postoperative events varied by outcome (reoperation: 517 [1.27%] vs 380 [0.93%]; risk ratio [RR]: 1.36 [95% confidence interval [CI], 1.19 to 1.55], endoscopic intestinal hemostasis: 17 [0.04%] vs 80 [0.20%]; RR: 0.21 [95% CI, 0.13 to 0.36]). Conclusion SA is becoming more common in colectomy. The risk of reoperation could be higher in the HA group, while the risk of postoperative endoscopic intestinal hemostasis could be higher in the SA group.